2001
DOI: 10.4049/jimmunol.167.5.2791
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility of Decay-Accelerating Factor Deficient Mice to Anti-Glomerular Basement Membrane Glomerulonephritis

Abstract: To prevent complement-mediated autologous tissue damage, host cells express a number of membrane-bound complement inhibitors. Decay-accelerating factor (DAF, CD55) is a GPI-linked membrane complement regulator that is widely expressed in mammalian tissues including the kidney. DAF inhibits the C3 convertase of both the classical and alternative pathways. Although DAF deficiency contributes to the human hematological syndrome paroxysmal nocturnal hemoglobinuria, the relevance of DAF in autoimmune tissue damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 59 publications
7
63
0
2
Order By: Relevance
“…DAF is a GPI-bound complement regulatory protein that also inhibits the C3 convertase enzymes. Mice with a targeted deletion of the GPI-DAF (Daf1) gene, when injured by subnephritogenic doses of anti-glomerular basement membrane antibody in the ANTN model, developed glomerular disease that was absent in controls (36). Overall, these studies demonstrated that regulation of C3 activation is important in preventing renal damage but did not clarify whether tissue injury is mediated by the anaphylatoxins C3a and C5a or via lytic or sublytic MAC insertion.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…DAF is a GPI-bound complement regulatory protein that also inhibits the C3 convertase enzymes. Mice with a targeted deletion of the GPI-DAF (Daf1) gene, when injured by subnephritogenic doses of anti-glomerular basement membrane antibody in the ANTN model, developed glomerular disease that was absent in controls (36). Overall, these studies demonstrated that regulation of C3 activation is important in preventing renal damage but did not clarify whether tissue injury is mediated by the anaphylatoxins C3a and C5a or via lytic or sublytic MAC insertion.…”
Section: Discussionmentioning
confidence: 78%
“…Among the several factors that have been implicated in the pathogenesis of this disease, the roles of Fc␥ receptors (34) and complement (35)(36)(37) have been most comprehensively investigated. Although the involvement of Fc␥ receptors in immune complex-mediated nephritis is well documented, the role of complement in this model is still controversial.…”
mentioning
confidence: 99%
“…During the preparation of this article, a report appeared by Sogabe and associates (Sogabe et al, 2001) that examined the effect of DAF deficiency in a model Electron microscopic examination of glomeruli from wild-type mice given NTS (A) show generally intact epithelial podocytes, with only segmental flattening and fusion (right side of field). In contrast, the epithelial podocytes in the knock-out mice given NTS (B) show extensive flattening and fusion and focal lipid vacuole formation (original magnification, ϫ20,000).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the findings described in this study, they similarly observed greater susceptibility to glomerular damage in Daf1 knock-out mice relative to wild-type controls despite equal renal expression of Crry. The predominant effect of DAF-deficiency in the studies by Sogabe et al (2001) seemed to be an increase in glomerular cellularity. Albuminuria was absent in the wild-type control mice and was mildly but significantly increased in the knock-out mice.…”
Section: Lin Et Almentioning
confidence: 99%
“…13,14 These mice were originally on a mixed C57BL/6 and 129 background, and were backcrossed onto the Balb/c strain for at least 10 generations. Homozygous DAF KO and CD59 KO mice were generated by intercrossing heterozygous mice and screened by flow cytometry as described.…”
Section: Materials and Methods Protocols For Animal Workmentioning
confidence: 99%